1995
DOI: 10.1161/01.cir.91.7.1936
|View full text |Cite
|
Sign up to set email alerts
|

RR Variability in Healthy, Middle-Aged Persons Compared With Patients With Chronic Coronary Heart Disease or Recent Acute Myocardial Infarction

Abstract: All measures of RR variability were significantly and substantially higher in healthy subjects than in patients with chronic or subacute coronary heart disease. The difference between healthy middle-aged persons and those with coronary heart disease was much greater 2 weeks after myocardial infarction than 1 year after infarction, but the fractional distribution of total power into its four component bands was similar for the healthy group and the two coronary heart disease groups. Values of RR variability pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
173
1
14

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 389 publications
(216 citation statements)
references
References 21 publications
27
173
1
14
Order By: Relevance
“…Many studies have also shown that even an alteration of cardiac ANS activity towards a predominance of adrenergic tone is associated with an increased risk of cardiac events in several disease settings [9][10][11][12], including diabetes [34].…”
Section: Inflammation and Cardiac Autonomic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have also shown that even an alteration of cardiac ANS activity towards a predominance of adrenergic tone is associated with an increased risk of cardiac events in several disease settings [9][10][11][12], including diabetes [34].…”
Section: Inflammation and Cardiac Autonomic Functionmentioning
confidence: 99%
“…Moreover, markers of inflammation predict cardiovascular events in several disease states [4][5][6]. Increased platelet activation [7,8] and sympathovagal imbalance of cardiac autonomic nervous system (ANS) activity [9][10][11][12] are also well-known predictors of acute coronary events.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is a decrease in HRV with advancing age [2][3][4][5][6] and that this reduction is associated with the emergence or worsening of cardiovascular disease, increasing the risk of death from all causes [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Changes of neural heart modulation occur in several systemic diseases, such as diabetes (2)(3)(4)(5), hypertension (6), heart failure (7,8), and coronary heart disease (9,10). In such situations, HRV analysis can be used to monitor long-term changes of cardiac regulation by the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%